Pathological findings of post-anesthetic myopathy associated with type 1 polysaccharide storage myopathy in a percheron horse - Fredo, Gabriela; Bassuino, Daniele Mariath; Bianchi, Matheus Viezzer; Delfiol, Diego José Zanzarini [UNESP]; Borges, Alexandre Secorun [UNESP]; Pavarini, Saulo Petinatti; Sonne, Luciana; Driemeier, David (My University, 2018)
Background: Post-anesthetic myopathy is the most common complication associated with general anesthesia in horses. Polysaccharide storage myopathy (PSSM) is characterized by an abnormal accumulation of glycogen and glycogen-related polysaccharides in the skeletal muscle, which is categorized in type 1 (PSSM1) and type 2 (PSSM2). The purpose of this study is to report the clinical, pathological and molecular findings in a Percheron mare with post-anesthetic myopathy associated with a PSSM1. Case: A 9-year-old Percheron mare was submitted to a caesarean section due to clinical dystocia during labor. Xylazine was employed during pre-anesthesia, followed by induction with ketamine and diazepam, while anesthetic maintenance was obtained with isoflurane. The mare showed good recovery, however 24 h later, sternal recumbency and hyperthermia (41° C) were observed. The mare was euthanized, and a necropsy was performed. Samples of multiple tissues were collected and routinely processed for histology. At necropsy, segments of skeletal muscles had bilateral pale areas. The kidneys had old and recent infarcts. The heart had whitish areas in the myocardium. The brain showed focally extensive reddish areas, with flattening of gyri. Histologically, skeletal muscle fibers had in the sarcoplasm multiple homogeneous globular clear eosinophilic formations, in addition to mild hyaline necrosis. In the heart and in the kidney, there were extensive areas of acute coagulative necrosis. The brain showed marked multifocal fibrinoid degeneration of vessels and hemorrhage. Refrigerated liver samples were submitted to DNA extraction to detect mutations in the GYS1 (type 1 PSSM) and RyR1 genes (malignant hyperthermia). A positive result for a homozygous dominant mutation in GYS1 (type 1 PSSM) was observed, while the mutation responsible for malignant hyperthermia was not identified. Discussion: The diagnosis of post-anesthetic myopathy associated with PSSM was obtained by the presence of amylase resistant polysaccharide complex inclusions, glycogen subsarcolemmal aggregates, and central cytoplasmic corpuscles containing glycogen through PAS-amylase resistant histochemical technique, associated to the myopathy microscopical features. Microscopic findings were related to clinical history, and the diagnosis of PSSM underlying post-anesthetic myopathy was determined. The predisposition of the Percheron horse has been described as an inherited predisposition leading to PSSM susceptibility, as was observed in the present case. We speculated that the anesthetic procedure resulted in the precipitation of the drug and a presentation of an acute anesthetic myopathy, while the muscle damage most likely occurred due to the ischemia caused by systemic hypotension. In addition to these lesions, other lesions were considered related to the use of the anesthetics, which may predispose to vasculogenic injuries. This horse was diagnosed as being homozygous dominant for the GYS1 gene, which causes a gain-of-function and results in glycogenolysis with glycogen accumulation in myofibers. Horses that are homozygous for the GYS1 gene may exhibit more severe histological changes in the skeletal muscle fibers, such as necrosis, anisocytosis, endomysial fibrosis, and fatty infiltration. In PSSM, there is a bilateral involvement of the skeletal muscles with areas of degeneration of whitish or greyish coloration, as well as pale muscle with whitish streaks due to coagulative necrosis and edema. In our study, we observed bilateral skeletal muscle lesions and cardiomyocyte necrosis. Post-anesthetic myopathy, along with skeletal muscle lesions, may predispose to vasculogenic injuries, with kidney and brain lesions in horses. Dominant homozygosis for the GYS1 gene with consequent PSSM1 disease probably aggravated the condition in this Percheron, with more severe histological muscular lesions. Our study should bring attention to the use of anesthetics in horses with PSSM1, especially in the Percheron breed.
Keywords: Horses; Metabolic disease; Periodic acid-Schiff; PSSM; Skeletal muscle diseases